335. Uncertainty in quantification of cumulative activity in bone metastasis dosimetry with 223Ra. (December 2018) - Donnarumma, R.; Ghidini, M.; Toselli, G.; Prandini, N.; Franceschetto, A.; Guidi, G.; Costi, T.
Abstract : Purpose: Ra-223 therapy of prostate cancer bone metastases is being used to treat patients routinely. Accurate activity quantification through imaging is essential to calculate the absorbed dose in organs and sub-units in radiopharmaceutical therapy, enabling personalized absorbed dose-based treatment planning methodologies and more effective and optimal treatments. This work was aimed to estimate the error in quantifying cumulated activity in simulated case applying specific SPECT calibration procedure[1, 2] . Methods: Calibrations with Ra-223 were performed with the SPECT/CT Infinia Hawkeye 4 GE (3/8-inch crystal) acquiring planar static images with double-peak (82 and 154 keV, 20% wide) and MEGP collimator. The sensitivity was measured in air by varying activity, source–detector distance, and source diameter. Acquisition times were 10 min. Transmission curves were measured for attenuation and scatter correction with the pseudo-extrapolation number method. A real case has been simulated placing on the source a bone equivalent material and PMMA thickness simulating human condition. Results: The calibration factors is 63.4 cps/MBq. The table attenuation affects less than 11.5%. Sensitivity values for each head varies by 0.4% respect to the mean value with the source-detector distance and the activity. The effect of the partial volume decreases the calibration factor of the smaller source by 10%. The quantified activity in the real case differs by less than 15% respect to the measured activity. Conclusions: The calibration factor found is higher than the literature value (45.7 cps/MBq[2] ). This result and the variation of the sensibility factor with source and acquisition setup stress the needed to characterize the system to perform a proper dosimetry estimation for any SPECT scanner. The error in determining the cumulated activity is less than 15%. Further studies including variation in source depth and acquisition time are needed to confirm these results including analysis in anthropomorphic phantom or human.